Development of Green Sukuk in Indonesia Based on The Pillars of Sustainable Development - Indar Fauziah Ulfah; Muhammad Fakhri Al-Kahfi (Perisai : Islamic Banking and Finance Journal, 2026)
Green Sukuk represents a transformative Islamic financial instrument specifically designed to fund environmentally friendly projects that accelerate the achievement of the Sustainable Development Goals (SDGs). Despite its potential, the issuance and management of Green Sukuk in Indonesia still encounter several operational clusters that require further optimization. This research aims to provide a comprehensive literature review regarding the development of Green Sukuk in Indonesia, analyzed through the framework of the SDGs Pillars (Social, Economic, Environmental, and Governance). The methodology employed is a qualitative literature review, utilizing a three-stage data analysis technique: data reduction, data display, and conclusion drawing/verification. The findings reveal that Green Sukuk plays a pivotal role as a catalyst for the sustainable development agenda and climate change mitigation. However, the instrument faces significant structural hurdles, including liquidity constraints in secondary markets, the risk of greenwashing, and the necessity for more rigorous impact reporting standards. The study concludes that while Green Sukuk is a vital financing bridge, further empirical research is essential to examine its practical implementation and ensure measurable contributions toward achieving Indonesia's 2030 SDG targets. Keywords: Green Sukuk, SDGs, Islamic Finance, Climate Change